Pemetaan Elemen MOOC Berdasarkan Desain Instruksional - El Vionna Laellyn Nurul Fatich; Paulus Insap Santosa; Ridi Ferdiana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
MOOC (Massive Open Online Course) is an innovation in the field of online learning that has been popular since 2012. MOOC users during the COVID-19 pandemic increased dramatically, but the dropout rate for MOOC was also high. One of the things that causes the high dropout rate is the MOOC design. To get a good MOOC design, it is necessary to design an instructional design. Instructional design is a guide in designing instruction or learning stages to facilitate effective learning so that learning objectives can be achieved. Many examples of instructional design have been introduced in previous studies, one of which is